Supervolcano - Mitchell, Tony.; Orr, Ailsa (London : BBC Worldwide, 2005)
"It's the near future and the world finally wakes up to the ultimate threat - not nuclear war or a terrorist attack - but the eruption of a gigantic 'supervolcano' simmering beneath Yellowstone Park. This factual drama tells the story of a devastating disaster waiting to happen."--Container.
Keywords: Supervolcanoes -- Yellowstone National Park -- Drama; Volcanic eruptions -- Yellowstone National Park -- Drama; Volcanoes -- Yellowstone National Park -- Drama